2023
DOI: 10.1002/jssc.202201059
|View full text |Cite
|
Sign up to set email alerts
|

State‐of‐the‐art molecular imprinted colorimetric sensors and their on‐site inspecting applications

Abstract: Molecular imprinted colorimetric sensors can realize visual semi-quantitative analysis without the use of any equipment. With the advantages of low cost, fast response, ease of handling, and excellent recognition ability, the molecular imprinted colorimetric sensor shows great application potential in the field of sample rapid assay. Molecular imprinted colorimetric sensors can be prepared in various forms to meet the needs of different sample determination, such as film, hydrogel, strip, and adsorption coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Furthermore, the sample's composition must be straightforward, and color rendering should be resistant to interferences. Nevertheless, the unique combination of the colorimetric sensor with MIT can remarkably address this drawback, allowing for the analysis of more complex samples with great potential for practical applications [145]. Since MICSs are widely used to determine various contaminants, some interesting reports are presented as follows, divided into four categories: food safety, environmental analysis, biological sample detection, and drug detection and medical treatment.…”
Section: Colorimetric Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the sample's composition must be straightforward, and color rendering should be resistant to interferences. Nevertheless, the unique combination of the colorimetric sensor with MIT can remarkably address this drawback, allowing for the analysis of more complex samples with great potential for practical applications [145]. Since MICSs are widely used to determine various contaminants, some interesting reports are presented as follows, divided into four categories: food safety, environmental analysis, biological sample detection, and drug detection and medical treatment.…”
Section: Colorimetric Methodsmentioning
confidence: 99%
“…Thus, the detection methods for food safety in daily life must provide good selectivity, low cost, low LODs, high sensitivity, easy portability, handling, and, most importantly, minimal reliance on instrumentation. These values can be achieved via the use of MICSs [145].…”
Section: Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensor was efficient, the binding analysis when MIP was immersed in 1–100 nM BPA showed that the binding sites in the MIP were not uniform, with one type of binding sites with high affinity and the other types with low affinity. Furthermore, Wang et al wrote an interesting review on the fabrication and the advantages of the combination of colorimetric sensors and MIP sensors to obtain molecularly imprinted colorimetric sensors (MICSs) [ 83 ]. Furthermore, Hamed and Li wrote a review on MIP-based sensors for bisphenol A [ 84 ].…”
Section: Detection Of Skeletal and Cardiac Muscle Analytes With Mipsmentioning
confidence: 99%
“…2 The colorimetric detection operation is simple and low-cost and has high detection sensitivity, high selectivity and anti-interference ability. 3 Shu et al 4 used TMB (3,3′,5,5′-tetramethylbenzidine) as a colorimetric probe to detect ascorbic acid (AA). In a weakly acidic medium, Ag + oxidized TMB to oxidized TMB (ox-TMB) and produced a solution with a blue absorption peak centered at 652 nm.…”
Section: Introductionmentioning
confidence: 99%